Risk Factors of Iron Deficiency Anemia among Children under Two Years Old in the Southeast of Iran: A Case-Control Study - Fatemeh Setoodehzadeh; Kosar Rezaei; Mohammad Khammarnia; Zeinab Almasi; Mostafa Peyvand (Shiraz University of Medical Sciences, 2024)
Background: Iron deficiency anemia in children is one of the most important challenges in the global health system. Also, it is one of the main problems in Iran, especially in the southern regions. Therefore, the aim of this study was to investigate the factors affecting iron deficiency anemia in children under two years of age.Methods: This case-control study was conducted on children under two years of age in Sistan and Baluchestan Province in the southeast of Iran with the highest birth rate in 2020. In the study, 760 children were divided into case and control group (380 vs 380). A standard information form was used for collecting data, and the data were analyzed using SPSS-21 by chi-square test and logistic regression.Results: There were significant associations between the child's iron deficiency anemia and the type of child nutrition (P=0.000), history of child's food allergies (P=0.021), child's congenital anomalies (P=0.009), maternal body mass index (P=0.083), number of previous pregnancies (P=0.035), history of abortion and stillbirth (P=0.027), use of postpartum supplementation (P=0.004), mother's anemia (P=0.000), family marriage (P=0.001), father's job (P=0.017), father's anemia (P=0.000), and father's addiction (P=0.007). Also, based on multivariate regression, the most important predictor of iron deficiency anemia in children was father's addiction (OR=1.720; 95% CI: 1.067 - 2.773).Conclusion: The findings showed that parental factors could play an important role in causing iron deficiency anemia in children. These risk factors can be improved and prevented by promoting health education, increasing parental awareness and knowledge, and improving the lifestyle of families. Therefore, holding educational and counseling classes for parents is especially recommended.